Pathogenesis, Diagnosis, Treatment and Prevention Strategies of Human Coronavirus: A Review (Bangladesh Journal of Infectious Diseases, 2020)
Coronaviruses is a group of virus which infects many species of animals, including humans. The rapid outbreak of COVID-19 raised serious attention at national and international levels and it was recognized as a pandemic by the World Health Organization. The disease model comprised of three different phases: replication of virus, hyperactivity of immune system and pulmonary cells destruction. For the diagnosis of asymptomatic carriers, viral nucleic acid (RNA) can be detected by using pharyngeal swab. Isolation of infected persons prevents the transmission and spread risk of the disease. Therapy includes use of oxygen therapy, high-flow nasal cannula (HFNC) and methylprednisolone (IV) and in severe cases adrenaline (IV). Anti-viral drugs such as ritonavir plus lopinavir per-orally and antibiotics (moxifloxacin or any antibiotic) were administered by IM/IV route to prevent secondary bacterial infection. Education campaigns are launched to promote different precautionary measures to avoid disease transmission.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S34-S37